Age stratified comparative analysis of perioperative, functional and oncologic outcomes in patients after robot assisted radical prostatectomy – A propensity score matched study. Issue 7 (July 2015) - Kumar, A.; Samavedi, S.; Bates, A.S.; Cuevas, Camilo A. Giedelman; Coelho, R.F.; Rocco, B.; Palmer, K.; Patel, V.R.
Abstract Introduction and objectives Our goal was to evaluate the perioperative, functional and intermediate term oncological outcomes of robot assisted radical prostatectomy (RARP) in patients ≥70 years. Materials and methods The study population (N = 3241) consisted of consecutive patients who underwent RARP for localized prostate cancer by a single surgeon (VP) from January 2008 through February 2012. A query of our Institutional Review Board approved registry identified 400 men ≥70 years of age, with good functional status (Charlson co-morbidity index <3). These patients were propensity score matched to younger patients. Perioperative and postoperative functional and oncologic outcomes for the two groups were compared. Results Full nerve sparing as well as the ease of nerve sparing were similar in 2 groups. Intra-operative complications were comparable. Postoperative complication occurrence rates were similar. At mean follow up of 34.1 months and 37.2 months respectively in younger and older patients, the continence rate was comparable in 2 groups (91.3% and 87.3%).Average time to continence and potency were similar in 2 groups. A greater proportion of younger patients became potent than elderly (52.3% vs 33.5%, p < 0.001).The biochemical recurrence (BCR) rate was comparable in 2 groups (7.8% vs 8.3%; p = 0.79). The mean time to BCR was also comparable in 2 groups (16 months vs 22.6 months; p = 0.07). Conclusions In appropriately selected patients (minimal comorbidities with CCI ≤2, life expectancy >10 years, localized prostate cancer) RARP is a reasonable option in patients ≥70 years and provides comparable perioperative, functional and intermediate term oncologic outcomes as compared to younger patients.